Gastrointestinal helminths of wolves (Canis lupus Linnaeus, 1758) in Piedmont, north-western Italy. (2020) - de Macedo, M.R.P.; Zanet, S.; Bruno, S.; Tolosano, A.; Marucco, F.; Rossi, L.; Muller, G.; Ferroglio, E.
Abstract: Free-ranging grey wolves ( Canis lupus ), which are presently recolonizing Italy, can be parasitized by a diversity of helminths, but have rarely been subject to studies of their parasites. Therefore, this study aims to determine the prevalence of gastrointestinal helminths of road-killed grey wolves from the Piedmont region of Italy. Forty-two wolves were collected and examined for the presence of helminths. We recorded 12 helminth species: nine Nematoda and three Cestoda. The nematodes were: Ancylostoma caninum (7.1%), Capillaria sp. (2.4%), Molineus sp. (2.4%), Pterygodermatites affinis (11.9%), Physaloptera sibirica (9.5%), Toxocara canis (9.5%), Toxascaris leonina (2.4%) and Uncinaria stenocephala (26.2%); the cestodes were: Dipylidium caninum (4.8%), Mesocestoides sp. (4.8%) and Taenia multiceps (76.2%). Physaloptera sibirica had the highest mean intensity and T. multiceps had the highest prevalence. Based on age and sex, no differences in the intensity or prevalence of helminth species were found among the hosts. Molineus sp. was recorded for the first time in wolves from the Palearctic region; P. affinis and P. sibirica are respectively reported for the first time in wolves from Europe and Italy.